Synthesis and Characterisation of Polyvinyl pyrrolidone/polyacrylamide (PVP/PAAm) Hydrogels via Hybrid Process: Morphological and Physical Properties, and Antibacterial Activity - Parın, Fatma Nur (My University, 2023)
Hydrogels are three-dimensional networks that constitute either chemical or physical crosslinks. Hydro- gels have been used in a variety of applications from biomedical and tissue engineering to wastewater treatment, and robotics. In recent years, many studies have shown that hydrogels are suitable for wound treatment in many respects. While hydrogels keep the wound warm, moist, and closed, the bioactive agents in their composition have an antibac- terial activity. Terpenes and terpenoids are natural-based materials which have been reported to have potent antibac- terial activity against different pathogens. However, poor solubility, sensitivity to external conditions, and volatility properties of them restrict them use as a wound healing agent. For this purpose, terpenes and terpenoids can be loaded into carrier matris such as hydrogels and they used as a wound dressing. In this study, the preparation of polyvinyl pyrrolidone/polyacrylamide (PVP/PAAm) hydrogels exhibiting antibacterial properties was demonstrated. Bio-deri- ved terpenes and terpenoid (?-bisabolol, d-limonene, and geraniol) were utilized as antibacterial agents, whereas stabilization of PVP/PAAm hydrogels was achieved by using beta-cyclodextrin (?-CD). PVP/PAAm polyblend so- lutions were polymerized via UV irradiation (photopolymerization). Then freeze-thawing and anneal-swelling were respectively carried out. Once the morphological, and physical properties of the resulting hydrogels were characteri- zed antibacterial efficiency tests were also performed. In the end, it was demonstrated that PVP/PAAm/?-bisabolol and PVP/PAAm/geraniol hydrogels have good antibacterial properties against Escherichia coli with 9 mm zone in- hibition.
Keywords: Freeze-thawing; Antibacterial efficiency; PVP/PAAm hydrogel; terpene and terpenoids; UV irradiation